PROTOCOL: Bereavement Interventions for Children and Adolescents: An Evidence and Gap Map of Primary Studies and Systematic Reviews - Leonor Rodriguez; James Lyons; Amy Maloy; Ailsa O'Brien (Campbell Systematic Reviews)
ABSTRACT This is the protocol for a Campbell evidence and gap map. The objectives are as follows: (1) To identify and map all existing primary studies and systematic reviews (published and unpublished) on bereavement interventions/programmes for children and adolescents to create a live, searchable and publicly available EGM; (2) Provide a comprehensive descriptive overview of psychosocial outcomes targeted by bereavement interventions for children and adolescents; (3) Determine the characteristics of bereavement interventions targeted at children and adolescents, including age, location, duration, delivery, underlying theories, evaluation and target death.